2018
DOI: 10.1016/j.micres.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors Atf1 and Sty1 promote stress tolerance under nitrosative stress in Schizosaccharomyces pombe

Abstract: Nitric Oxide (NO) and its associated reactive nitrogen species (RNS) produce nitrosative stress under various pathophysiological conditions in eukaryotes. The fission yeast Schizosaccharomyces pombe regulates stress response mainly through the Sty1-Atf1 MAP Kinase pathway. The present study deals with the role of transcription factor Atf1 and Sty1 in S. pombe under nitrosative stress. In this study, exposure to an NO donor resulted in S-phase slowdown with associated mitotic block in S. pombe. Deletion of sty1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Fungi have developed detoxification strategies to counteract the damaging effects of NO and the ROS‐responsive transcription factors also play protective important roles. For example, in S. pombe Atf1 is a key player for the initiation of the S‐phase in the cell cycle, allowing a pause in replication to respond to nitrosative stress (Kar et al ., 2018). In S. cerevisiae Yap1 is a key regulator in response to nitrosative stress by up‐regulating expression of superoxide dismutase and catalase (Lushchak et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi have developed detoxification strategies to counteract the damaging effects of NO and the ROS‐responsive transcription factors also play protective important roles. For example, in S. pombe Atf1 is a key player for the initiation of the S‐phase in the cell cycle, allowing a pause in replication to respond to nitrosative stress (Kar et al ., 2018). In S. cerevisiae Yap1 is a key regulator in response to nitrosative stress by up‐regulating expression of superoxide dismutase and catalase (Lushchak et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, VdAtf1 is critical to an appropriate response to NO stress by regulating the transcription of genes involved in NO detoxification in V. dahliae , and an FgAtf1 mutant strain of Fusarium graminearum displayed increased sensitivity to NO (Tang et al ., 2020). In Schizosaccharomyces pombe , Atf1 accumulates in the nucleus in response to nitrosative stress to promote stress tolerance (Kar et al ., 2018), while in Saccharomyces cerevisiae , Yap1 also accumulates in the nucleus under nitrosative stress and mediates the changes in gene expression that correlate with RNS‐induced responses (Horan et al ., 2006; Lushchak et al ., 2010). Nevertheless, little is known about how Skn7 homologs mediate responses to RNS.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that AtfA/Atf1 and its orthologs are quite highly conserved and that they are involved in multiple cellular processes. In S. pombe, Atf1 regulates the transcription of genes involved in recombination at some hot spots and in the initiation of the mating and meiosis processes, survival at stationary phase (20), heterochromatin assembly, and responses to osmotic, heat, starvation, and nitrative stress (19,21,22). In filamentous fungi, AtfA/Atf1 regulates the expression of genes related to conidial stress in Aspergillus fumigatus, Aspergillus nidulans, and Aspergillus oryzae (23)(24)(25)(26), genes related to vegetative hyphae and/or secondary metabolism in A. nidulans (27,28), Botrytis cinerea (29), Claviceps purpurea (30), Fusarium graminearum (31), Fusarium oxysporum (32), and Magnaporthe oryzae (33), and fungal virulence in B. cinerea, C. purpurea, F. graminearum, and M. oryzae (29,30,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that Atf1 is involved in regulating the cell cycle checkpoint activation in S. pombe upon nitrosative stress [25]. To decipher the function of Atf1 and Pcr1 in S. pombe upon nitrosative stress, in the present study we rst time show that phosphorylation of Atf1 is not essential for replication checkpoint initiation, Atf1 and Pcr1 can function independently and play an antagonistic role in cell growth regulation.…”
Section: Introductionmentioning
confidence: 50%